Mewujudkan Livable City: Persepsi Tentang Ruang Terbuka yang Aman dan Tidak Aman di Kota Bandung - Kusuma, Yudhistira; Aryanti, Tutin; Megayanti, Trias (RUAS, 2023)
The Bandung City Government strives to create a comfortable city space for its citizens. Preliminary studies show that not all city residents use city parks. This study aims to explore the perception of city residents about the safety of public spaces in Bandung City. The research was conducted by combining quantitative methods using questionnaires with qualitative methods through observation and documentation of places that were considered the safest and least safe from the results of the questionnaire. The results showed that places that are considered safe have an excellent level of neatness and cleanliness, equipped with street and garden furniture devices, large pedestrian areas, and attractive to be photo spots. Places that are perceived as unsafe are places that lack clear use and function, have a poor level of service, and are in areas that have low visibility. Recommendations for the redesign of unsafe places are presented by integrating built environment principles that can tackle crime.